The impact of rising maritime transport costs on international trade: Estimation using a multi-region general equilibrium model - Emanuele Ferrari; Panayotis Christidis; Paolo Bolsi (Transportation Research Interdisciplinary Perspectives, 2023)
This paper evaluates the impact of the 2021–22 surge in rates for containerized and bulk shipping costs. Employing a detailed transport database and applying a set of detailed shocks by transportation mode, regions and commodities in a multi-region general equilibrium model, the paper analyses the sectorial (agri-food sectors, manufacturing) and macroeconomic (trade, wide-economic indicators) impacts of the recent surge in shipping costs. Maritime transport costs are sensitive to imbalances between global demand and supply, which rose further after the Covid-19 pandemic. In a globalised world, an increase in shipping rates can have widespread repercussions on international trade, creating risks for the global economic activity. The results allow the analysis of how shocks in transport costs can affect prices in international trade and explain the short- and medium-term impacts on the economy. The main finding is that rising maritime transport costs tend to reverse the trend towards globalisation of international trade and favour localization.